Transcriptomic Analysis of Gene Networks Regulated by U11 Small Nuclear RNA in Bladder Cancer - Wang, Zhenxing; Wang, Xi; Wang, Yaobang; Tang, Shaomei; Feng, Chao; Pan, Lixin; Lu, Qinchen; Tao, Yuting; Xie, Yuanliang; Wang, Qiuyan; Tang, Zhong (Frontiers in Genetics, 2021)
Small nuclear RNA is a class of non-coding RNA that widely exist in the nucleus of eukaryotes. Accumulated evidence showed that small nuclear RNA involves in the development of tumors. To explore the effect of gene network regulated by U11 small nuclear RNA on the occurrence and development of bladder cancer. U11 small nuclear RNA knockout and overexpression were performed on T24 bladder cancer cell line, and the gene expression of U11 knockout group, overexpression group and untreated control group were analyzed by RNA sequencing. The dysregulated expressed genes in the U11 knockout and overexpression groups were mainly enriched in tumor-related pathways, such as NF-kappa B signaling pathway, Bladder cancer and PI3K-Akt signaling pathway. In conclusion, U11 may alter gene expression by affecting the PI3K-Akt signaling pathway and NF-kappa B signaling pathway, regulating alternative splicing events of FN1 and RPL22L1, and ultimately leading to the development of bladder cancer.